Managing the risk in pension plans and recent pension reforms - Richard W. Kopcke (Federal Reserve Bank of Boston, 2007)
This paper examines the characteristics of three funding strategies for pension plans and analyzes the investment strategies that complement these strategies. Although the primary focus is on defined benefit plans, which include Social Security, it also applies to employees' defined contribution plans, which, when their beneficiaries set specific goals for their future retirement benefits, are essentially defined benefit plans. The findings suggest that pension plans should use interest rates on Treasury securities instead of yields on corporate bonds to calculate the value of their liabilities. Defined benefit plans, including Social Security, could stabilize the balance between the value of their assets and their obligations if they financed only the value of the benefits that their beneficiaries have accrued and they invested their assets in Treasury securities. In this case, the required contribution per dollar of wages would need to change significantly with the rate of growth of employment. By funding the obligation entailed by employees' projected income at retirement, contributions per dollar of wages would change less with the growth of employment. However, in this case, plans would need to invest in a broader range of assetsincluding Treasury inflation-protected securities, stocks, and real assetsto prevent the balance between their assets and liabilities from varying too greatly. Furthermore, plans would need to hold surplus assets to minimize the risk of becoming underfunded.
Keywords: G23; G28; G38; 330